Inclusive J/[psi] production in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Mercado Pérez, Jorge; et al. (Physics letters, 2018)
Inclusive J/ψ production is studied in Xe-Xe interactions at a centre-of-mass energy per nucleon pair of sNN=5.44 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed via its decay into a muon pair, in the centre-of-mass rapidity interval 2.5<y<4 and down to zero transverse momentum. In this Letter, the nuclear modification factors RAA for inclusive J/ψ, measured in the centrality range 0-90% as well as in the centrality intervals 0-20% and 20-90% are presented. The RAA values are compared to previously published results for Pb-Pb collisions at sNN=5.02 TeV and to the calculation of a transport model. A good agreement is found between Xe-Xe and Pb-Pb results as well as between data and the model.